Claims Behind Women’s Liberation - Alsaket, Khaldun Yousef Awwad (Journal of Islamic Sciences, 2021)
The Study Aimed to Clarify the Claims of Women’s Liberation and Also Dealt with Their Concept and Origin, and to Talk About the Most Prominent Advocates of Women’s Freedom’ And the Ideas and Belifs Advocated by The Advocates of Liberation and The Likes Raised Around Them. One of the Most Prominent Findings of the Study Is That Advocates of Women’s Liberation Are A Secular Movement That Emerged At The Beginning of The Ninteenth Century In The Arab Countries Of Egypt, And The Balance Of Liberation Among Advocates Of Liberation Is That Women Liberate From The Command Of Our Lord And Disobey God Almighty.